Synthesis of Flame-Retardant Polypropylene/LDH-Borate Nanocomposites - Wang, Q; Undrell, J; Gao, Y; Cai, G; Buffet, J; Wilkie, C; O'Hare, D (2013)
New nanocomposites have been prepared using unmodified polypropylene (PP) and a new type of highly dispersed [Zn2Al(OH6)][B 4O5(OH)4]0.5 (Zn2Al- borate) and [Mg3Al(OH)8][B4O 5(OH)4]0.5 (Mg3Al-borate) layered double hydroxides (LDHs). PP/LDHs nanocomposites with LDH loadings of 1, 3, 6, 9, 15, and 30 wt % have been prepared by a novel solvent mixing method. Scanning electron microscopy (SEM) analysis shows that the precipitated nanocomposites materials form spherical particles with an average size of ca. 10 μm and that the LDH nanoparticles were well dispersed within the PP matrix. XRD analysis of the nanocomposites indicates that the LDHs are completely exfoliated. The thermal stability and flame retardancy properties of these new materials have been evaluated as a function of the nature of LDH and the LDH loadings. Cone calorimetry analysis indicates that PP/Zn2Al-borate nanocomposites exhibited superior performance than the equivalent PP/Mg3Al-borate nanocomposites; a 15 wt % of the highly dispersed Zn2Al-borate LDH in PP was found to be the optimal loading. The 15% Zn2Al-borate LDH in pristine (unmodified) PP resulted in reduction of the PHRR (peak heat release rate) (Rdctn) by 63.7%. We also demonstrated that the solvent mixing is superior to a melt mixing method. With a 6 wt % LDH loading, the reduction in PHRR is 23.8% for the melt mixing sample, which is lower than that of solvent mixing sample (29.9%), this behaviour can be attributed to the severe aggregation and poor dispersion of LDH particles. © 2013 American Chemical Society.